Correlation between symptoms and objective findings may improve the symptom-based diagnosis of chronic rhinosinusitis for primary care and epidemiological studies. Issue 12 (16th December 2015) - Park, Do-Yang; Lee, Eun Jung; Kim, Ji Hoon; Kim, Yoo Suk; Jung, Chan Min; Kim, Kyung-Su
Abstract : Background: In primary care and epidemiological studies of chronic rhinosinusitis (CRS), symptom-based diagnosis is common, yet limited, because endoscopic and radiological signs are not considered. Objectives: To evaluate the correlation between symptoms and objective findings of CRS to improve its symptom-based diagnosis for primary care and epidemiological studies by using data from a large-scale nationwide epidemiological study, the Korean National Health and Nutrition Examination Survey (KNHANES). Design: Cross-sectional study. Setting: Data from 2008 to 2012 KNHANES. Participants: 29 225 Adults aged >19 years. Outcome measures: Questionnaires targeted two major (nasal blockage and anterior/posterior nasal drip) and two minor (facial pain/pressure and reduction or loss of smell) symptoms. Nasal polyps or mucopurulent discharge from the middle meatus was defined as positive endoscopic findings for diagnosing CRS. Results: Of the four symptoms, reduction or loss of smell was the symptom most significantly related to positive endoscopic findings in multivariable analysis (OR=1.936 (95% CI 1.604 to 2.337)). The combinations of symptoms showed higher ORs than individual symptoms and combinations of reduction or loss of smell with other symptoms were statistically more reliable for positive endoscopic findings than other combinations. Conclusions: Our results show that reduction or loss of smell was the symptom most significantly related to positive nasal endoscopic findings. Therefore, symptom-based diagnosis of CRS can be improved by considering reduction or loss of smell as an important symptom for positive endoscopic findings of CRS.